The dynamic evolution and obstacle identification of pseudo and reality human settlements in the central plains urban agglomeration of China - Yadan Wang; Shenzhen Tian; Hang Li; Xueming Li; Jun Yang; Wenmei Wu (Scientific Reports)
Abstract Exploring the development of human settlements is crucial in creating a “Beautiful China” accelerating central China region growth, improving human settlements geography research, and advancing the human-land system theory. This study constructs a theoretical framework for the coupling and coordination of pseudo and reality human settlements and takes the Central Plains Urban Agglomeration as the study area. It investigated the dynamic evolution and driving mechanisms of pseudo and reality human settlements in the Central Plains urban agglomeration using multi-source big data from online shopping, social communication, information search, and remote sensing images during 2011–2021 and conducted comprehensive, kernel density, coupling coordination degree, and obstacle degree analyses. The results show that: (1) Temporal development exhibited phased growth with disparities across dimensions. (2) Spatial patterns exhibited core-driven development, followed by “十”-shaped development and comprehensive “米”-shaped development. (3) The coupling coordination is on a growing trend, and the laddering development is clearly characterized. (4) Natural population growth rate and urbanization rate, etc. are the main obstacle factors of the reality human settlements; Taobao and Baidu maps, etc. are the main obstacle factors of the pseudo human settlements.